Hubungan Rasio Anterior dengan Overjet dan Overbite pada Perawatan Orthodontik - J. A. Budiman; E. D. D. Yashadana; S. D. Sadoso; P. I. Masbirin (Faculty of Dentistry, Universitas Indonesia, 2015)
The important role of the tooth size information is in making diagnosis and treatment plan of the cases with malocclusion. A lot of studies have been done in this aspect such as about tooth size with its variation, and also the ratio of maxillary to mandibular tooth size. The most famous tooth size analysis is Bolton analysis with his anterior ratio and overall ratio. Because the accordance of those ratio is not found in all orthodontic cases, some studies (Korbitz, Neff, Moyers and Steadman) tried to relate the anterior ratio with the amount of overjet and overbite in orthodontic treatment. Those relationship was found strong, but there are also other analysis that should be considered in treating orthodontic cases.